2017
DOI: 10.1371/journal.pone.0185594
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the individual risk of fecal poliovirus shedding among vaccinated and non-vaccinated subjects following national health weeks in Mexico

Abstract: BackgroundMexico introduced inactivated polio vaccine (IPV) into its routine immunization (RI) schedule in 2007 but continued to give trivalent oral polio vaccine (tOPV) twice a year during national health weeks (NHW) through 2015.ObjectivesTo evaluate individual variables associated with poliovirus (PV) shedding among children with IPV-induced immunity after vaccination with tOPV and their household contacts.Materials and methodsWe recruited 72 children (both genders, ≤30 months, vaccinated with at least two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
(20 reference statements)
0
4
0
Order By: Relevance
“…SL2 was the most frequently detected PV during tOPV use. While SL1, SL2 and SL3 are shed at similar rates, SL2 circulates more widely among unvaccinated individuals, thus increasing SL2 environmental prevalence (Troy et al 2014;Ferreyra-Reyes et al 2017), and possibly contributing to frequent SL2 detection. After the switch to bOPV, SL2 detection decreased, suggesting its absence from the environment following OPV2 withdrawal in Nairobi.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SL2 was the most frequently detected PV during tOPV use. While SL1, SL2 and SL3 are shed at similar rates, SL2 circulates more widely among unvaccinated individuals, thus increasing SL2 environmental prevalence (Troy et al 2014;Ferreyra-Reyes et al 2017), and possibly contributing to frequent SL2 detection. After the switch to bOPV, SL2 detection decreased, suggesting its absence from the environment following OPV2 withdrawal in Nairobi.…”
Section: Discussionmentioning
confidence: 99%
“…2014; Ferreyra‐Reyes et al . 2017), and possibly contributing to frequent SL2 detection. After the switch to bOPV, SL2 detection decreased, suggesting its absence from the environment following OPV2 withdrawal in Nairobi.…”
Section: Discussionmentioning
confidence: 99%
“…Given that the overall rate of shedding was low in all studies, 2.4% in the pilot (Troy et al, 2011) and 6% in the larger prospective study (Troy et al, 2014), the re-classification of the S2 false positives would further reduce the rate of shedding and would likely have limited impact on the overarching conclusions of these studies. For example, evaluation of both the original assay and the multiplex rRT-PCR revealed that shedding of OPV2 by household contacts was most likely the source of infection of non-vaccinated children and subjects older than 5 years of age living in the same household (Ferreyra-Reyes et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, widespread use of the vaccina virus against smallpox was originally associated with severe adverse events, prompting the development of second and then third generation vaccines to limit the number of persons who might experience adverse reactions 7 . In addition, current evidence shows that fecal shedding of the oral polio vaccine by vaccinated children has been associated with infection of unvaccinated children in the same household 8 .…”
Section: Introductionmentioning
confidence: 99%